2010
DOI: 10.1002/app.33081
|View full text |Cite
|
Sign up to set email alerts
|

Application of lime kiln dust as a filler in the natural rubber industry

Abstract: Lime kiln dust (LKD) obtained from kraft chemical recovery systems by conversion of calcium carbonate (CaCO 3 ) back into calcium oxide (CaO) for reuse in the causticizing process, is mainly composed of CaCO 3 . A two-stage conventional mixing procedure was used to incorporate LKD into natural rubber (NR). For comparison purposes, four commercial fillers, stearic acid coated CaCO 3 , ground CaCO 3 , silica, and carbon black, were also used. The effect of these fillers on the curing characteristics and mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…It is well known that polar aand nonpolar polymers form electrets with extremely long life and are less sensitive to temperature and environmental humidity. However, the greatest volume of work has been carried out with single layer polymers belonging to the polar and nonpolar class . Electronic transport in polymers has been investigated by many workers; both from scientific interest in large energy band gap systems and for engineering needs for electrical insulators .…”
Section: Introductionsupporting
confidence: 68%
“…It is well known that polar aand nonpolar polymers form electrets with extremely long life and are less sensitive to temperature and environmental humidity. However, the greatest volume of work has been carried out with single layer polymers belonging to the polar and nonpolar class . Electronic transport in polymers has been investigated by many workers; both from scientific interest in large energy band gap systems and for engineering needs for electrical insulators .…”
Section: Introductionsupporting
confidence: 68%
“…This corresponds to the CRI increasing with the amount of grafting due to crosslinking reactions via the sulfidic linkages together with reactions of polar functional groups between PHEA molecules . The polar functional groups of the grafted side chains could form hydrogen bonds with each other, accelerating vulcanization and curing rate …”
Section: Resultsmentioning
confidence: 99%
“…Arayapranee and Rempel examined the grafting of the olefinic monomers acrylonitrile, MMA and styrene onto NR, to enhance the polarity of the NR backbone in order to improve the silica−rubber interactions. It was found that the grafted NR provided significant improvements in resistance of the composites to heat, oil and ozone, while maintaining the mechanical properties of the rubber . Klinpituksa et al .…”
Section: Introductionmentioning
confidence: 99%
“…[2] as per reports cited in many works [3][4][5][6][7][8][9][10]. A wide range of the applications of rubber products can be manufactured, because they have the potential to combine the attractive properties of both constituents in the blend, when compared to the economic and technical uncertainties that are associated with synthesizing new polymeric materials [11].…”
Section: Introductionmentioning
confidence: 88%